2017 IEEE 86th Vehicular Technology Conference (VTC-Fall) 2017
DOI: 10.1109/vtcfall.2017.8288319
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Class Dispatching and Charging Scheme for Autonomous Electric Mobility On-Demand

Abstract: Despite the significant advances in vehicle automation and electrification, the next-decade aspirations for massive deployments of autonomous electric mobility on demand (AE-MoD) services are still threatened by two major bottlenecks, namely the computational and charging delays. This paper proposes a solution for these two challenges by suggesting the use of fog computing for AEMoD systems, and developing an optimized multi-class charging and dispatching scheme for its vehicles. A queuing model representing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…the higher the waiting time will be. Moreover, in previous related work [18] [19], we showed that increasing the number of classes n beyond its strict lower bound introduced in Lemma 2 in [18] will damage the system performance and increase the maximum response time. c , for different decision approaches namely our derived optimal decisions to the following decisions sets: 1) Optimized charging decisions (i.e.…”
Section: Simulation Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…the higher the waiting time will be. Moreover, in previous related work [18] [19], we showed that increasing the number of classes n beyond its strict lower bound introduced in Lemma 2 in [18] will damage the system performance and increase the maximum response time. c , for different decision approaches namely our derived optimal decisions to the following decisions sets: 1) Optimized charging decisions (i.e.…”
Section: Simulation Resultsmentioning
confidence: 95%
“…We proposed to resolve the first limitation, communication/computation delays, by suggesting the exploitation of the new and trendy fog-based networking and computing architectures [20]. The privileges brought by this technique [18], will allow handling instantaneous decision making applications such as AEMoD system operations in a distributed and accelerated way. The fog controller in each service zone is responsible of collecting information about customer requests, vehicle in-flow to the service zone, their state-of-charge (SoC), and the available full-battery charging rates in the service zone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we address the above vehicle dimensioning problem with bounded response time guarantees for the fogbased multi-class AEMoD management system proposed in [14]. Using a queuing model representing the multi-class charging and dispatching processes of each zone, we first derive the stability conditions and the number of system classes to guarantee the response time bound.…”
Section: Introductionmentioning
confidence: 99%